Transforming the discharge conversation through support and structure: A scoping review - Marie C. Haverfield; Gisselle De Leon; Angelica Johnson; Victoria L. Jackson; Geetali Basu; Jane Dodge (Elsevier, 2024)
Background: System level demands and interpersonal barriers can disrupt nurse delivery of high-quality information at discharge, which can contribute to a lack of caregiver preparedness to manage care of the patient and ultimately affect patient health. Objective: To synthesize evidence on effective nurse communication with informal caregivers during hospital discharge of adult patients with cognitive decline or Alzheimer's disease and related dementia. Design: A scoping review of inpatient nurse communication with informal caregivers. Methods: Collected research (published between 2011 and 2023) from three databases (MEDLINE, PsycINFO, and CINAHL), along with a separate search for gray literature (N = 18), to extract and synthesize recommended communication practices evidenced to improve the nurse care experience and support caregiver activation and preparedness. Results: Extraction synthesis of strategies resulted in two themes with corresponding sub-themes: Support (Information exchange, Space and time to determine preparedness, and Positive reinforcement of caregiver efforts) and Structure (Setting shared expectations, Informational resources, and Standardization). Conclusions: We offer practical recommendations for both interpersonal and policy level facilitation of nurse delivery of high-quality information at discharge to caregivers of patients with serious illness.